Study of serum vitamin D levels in men with premature androgenetic alopecia. (9th June 2020) - Sanke, Sarita; Samudrala, Suvarna; Yadav, Anuja; Chander, Ram; Goyal, Rajeev
Abstract: Background: Vitamin D deficiency had been associated with various hair loss disorders, such as telogen effluvium, alopecia areata, and female pattern hair loss. However, previous studies have not found a correlation between serum vitamin D levels and the severity of androgenetic alopecia. Methods: A case‐control study was conducted for a period of one year in a public tertiary care hospital. Fifty males clinically diagnosed with androgenetic alopecia and 50 age‐matched healthy controls were recruited. Serum vitamin D levels in both cases and controls were measured by radioimmunoassay technique, and the results were compared. Results: A total of 50 cases and 50 controls were recruited and analyzed. The mean age of the cases was 23 years and that of controls was 24.2 years. The mean levels of serum vitamin D significantly decreased in cases, compared to controls (20.10 vs. 29.34 ng/mL; P  ≤ 0.001). Eighty‐six percent of the cases had deficiency of vitamin D (<30 nmol/L), while 14% had insufficient vitamin D levels (31–50 nmol/L). There was a positive correlation between vitamin D deficiency and severity of androgenetic alopecia (AGA), which was statistically significant ( P  ≤ 0.5). However, there was no correlation between the duration of sun exposure and serum vitamin D levels (2.36 ± 1.2 in cases and 3.23 ± 1.6 in controls, P value = 0.98). Conclusion: Our study showed a significant correlation between vitamin D deficiency and the severity of androgenetic alopecia. This suggests that vitamin D may play a role in the premature onset of androgenetic alopecia. However, further studies on a larger population and the effect of vitamin D supplementation on the progression of androgenetic alopecia are required to validate the above findings.